Biology for dummies, portable edition - Siegfried, Donna Rae (Wiley Pub., 2006)
The Biology for Dummies book to everyday people or prospective students in the subject matter. It provides a good review of biology down to the cells and the beginning of life continuing to the inner workings of the human body.